Workshop Sintesis Minyak Angin sebagai Analgesik bagi Ibu-Ibu Gampong Peunayong Banda Aceh Kecamatan Kuta Alam - Lubis, Mirna Rahmah; Meilina, Hesti; Maimun, Teuku; Aflah, Nurul (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2024)
This community service has the aim of providing education by way of direct workshop. A total of 31 respondents in this community service activity were the people of Gampong Peunayong, Banda Aceh City, Kuta Alam District. Gampong Peunayong as the farthest village is seldomly supported by Banda Aceh government programs, thus the area is less independent. The service group has departed for this village to carry out workshop activities on making medicated oil. This medicated oil making workshop from the Engineering Faculty, Syiah Kuala University was designed because medicated oil has many uses, most of which can eliminate discomfort in the body. This community service is a description service activity through a cross sectional approach. The outputs of the community service activity are the production of medicated oil as an analgesic, increased knowledge of the people of Gampong Peunayong about the rational and wise use of medicated oil, the identification of qualified oil, as well as the drying of oil-producing plants. Based on the community service activity, it is concluded that education with workshops on making medicated oil has increased the skills and understanding of the community awareness and understanding of the community about using gandapura oil as an analgesic.